Exploring Pro-Inflammatory Immunological Mediators: Unraveling the Mechanisms of Neuroinflammation in Lysosomal Storage Diseases - Manoj Kumar Pandey (Biomedicines, 2023)
Lysosomal storage diseases are a group of rare and ultra-rare genetic disorders caused by defects in specific genes that result in the accumulation of toxic substances in the lysosome. This excess accumulation of such cellular materials stimulates the activation of immune and neurological cells, leading to neuroinflammation and neurodegeneration in the central and peripheral nervous systems. Examples of lysosomal storage diseases include Gaucher, Fabry, Tay–Sachs, Sandhoff, and Wolman diseases. These diseases are characterized by the accumulation of various substrates, such as glucosylceramide, globotriaosylceramide, ganglioside GM2, sphingomyelin, ceramide, and triglycerides, in the affected cells. The resulting pro-inflammatory environment leads to the generation of pro-inflammatory cytokines, chemokines, growth factors, and several components of complement cascades, which contribute to the progressive neurodegeneration seen in these diseases. In this study, we provide an overview of the genetic defects associated with lysosomal storage diseases and their impact on the induction of neuro-immune inflammation. By understanding the underlying mechanisms behind these diseases, we aim to provide new insights into potential biomarkers and therapeutic targets for monitoring and managing the severity of these diseases. In conclusion, lysosomal storage diseases present a complex challenge for patients and clinicians, but this study offers a comprehensive overview of the impact of these diseases on the central and peripheral nervous systems and provides a foundation for further research into potential treatments.